Influence of stochastic delay contaminations on IP network coordinate system and contamination mitigation methods - ZHANG Min1; ZHOU Liang2; HUANG Qiong3; YANG Xiao-long1; LONG Ke-ping1 (Tongxin xuebao)
There are various stochastic delay contaminations in the IP networks,which have a great impact on the per-formance of IP network coordinates system in terms of the delay prediction accuracy and the coordinate stability.Here,from the perspective of keeping the statistical characteristic of delay without a loss and suppressing the abnormal delay jitter,two contamination mitigation methods were proposed respectively,i.e.,t-Filter and Δ-Filter.Through the PlanetLab datasets,compared with MP-Filter,the simulation results show that both t-Filter and Δ-Filter can enhance the delay pre-diction accuracy,the system stability and the system convergence in the more effective methods.